Exciton‐Polaritons and Their Bose–Einstein Condensates in Organic Semiconductor Microcavities. Issue 4 (8th December 2021) - Jiang, Zhengjun; Ren, Ang; Yan, Yongli; Yao, Jiannian; Zhao, Yong Sheng
Abstract: Exciton‐polaritons are half‐light, half‐matter bosonic quasiparticles formed by strong exciton–photon coupling in semiconductor microcavities. These hybrid particles possess the strong nonlinear interactions of excitons and keep most of the characteristics of the underlying photons. As bosons, above a threshold density they can undergo Bose–Einstein condensation to a polariton condensate phase and exhibit a rich variety of exotic macroscopic quantum phenomena in solids. Recently, organic semiconductors have been considered as a promising material platform for these studies due to their room‐temperature stability, good processability, and abundant photophysics and photochemistry. Herein, recent advances of exciton‐polaritons and their Bose–Einstein condensates in organic semiconductor microcavities are summarized. First, the basic physics is introduced, and then their emerging applications are highlighted. The remaining questions are also discussed and a personal viewpoint about the potential directions for future research is given. Abstract : An overview of organic exciton‐polaritonics is given. First, the principle of polariton formation and polariton condensation is introduced. Then, recent experimental advances and emerging applications in organic semiconductor microcavities are reviewed. To conclude, some remaining questions are considered and a personal viewpoint about future directions in this field is provided.